2017
DOI: 10.1177/0960327117710534
|View full text |Cite
|
Sign up to set email alerts
|

Hypolipidemic and hepatoprotective activities of rosemary and thyme in gentamicin-treated rats

Abstract: Rosemary ( Rosmarinus officinalis; RM) and thyme ( Thymus vulgaris; TV) are used as remedies. We designed this work to investigate the preventive effect of aqueous extracts of RM or TV on the gentamicin (GM)-induced hepatotoxicity and abnormalities of lipid profile in rats. Both plant extracts exhibited an in vitro antioxidant activity as determined by the 1,1-diphenyl-2-picrylhydrazyl assay. Radical scavenging activity for TV extract was 48.7% and for RM extract was 25.6%. Polyphenolic determination by high-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 46 publications
3
21
0
Order By: Relevance
“…sore throat [ 162 , 163 ], skin inflammation [ 163 ], digestive and prokinetic [ 163 , 164 , 165 ], kidney problems [ 163 , 165 , 166 , 167 ], and anti-inflammatory [ 163 , 165 , 168 ]; Thymus spp. hypolipidaemic [ 144 ], balsamic and expectorant [ 169 , 170 , 171 , 172 ], and anti-inflammatory [ 170 , 171 ]; Urtica dioica hypolipidaemic, anti-atherosclerosis, hepatoprotective, and diuretic [ 173 , 174 ], anti-inflammatory, rheumatic pains, and contusions [ 65 , 173 , 174 , 175 , 176 ]; Vaccinium myrtillus maintenance of ocular health and function [ 146 , 177 , 178 , 179 , 180 , 181 , 182 , 183 , 184 ] (this last activity is refuted by a systematic review from 2004 [ 185 ]), improving of blood circulation [ 146 , 178 , 183 , 186 ], and maintaining of urinary tract health [ 187 ]; Vaccinium vitis-idaea maintaining of ocular health and function [ 180 , 181 ] and maintaining of urinary tract health [ ...…”
Section: Resultsmentioning
confidence: 99%
“…sore throat [ 162 , 163 ], skin inflammation [ 163 ], digestive and prokinetic [ 163 , 164 , 165 ], kidney problems [ 163 , 165 , 166 , 167 ], and anti-inflammatory [ 163 , 165 , 168 ]; Thymus spp. hypolipidaemic [ 144 ], balsamic and expectorant [ 169 , 170 , 171 , 172 ], and anti-inflammatory [ 170 , 171 ]; Urtica dioica hypolipidaemic, anti-atherosclerosis, hepatoprotective, and diuretic [ 173 , 174 ], anti-inflammatory, rheumatic pains, and contusions [ 65 , 173 , 174 , 175 , 176 ]; Vaccinium myrtillus maintenance of ocular health and function [ 146 , 177 , 178 , 179 , 180 , 181 , 182 , 183 , 184 ] (this last activity is refuted by a systematic review from 2004 [ 185 ]), improving of blood circulation [ 146 , 178 , 183 , 186 ], and maintaining of urinary tract health [ 187 ]; Vaccinium vitis-idaea maintaining of ocular health and function [ 180 , 181 ] and maintaining of urinary tract health [ ...…”
Section: Resultsmentioning
confidence: 99%
“…The toxicity caused by gentamicin was attenuated in Sprague-Dawley rats with administration of R. officinalis L. extract [60]. In this study, the animals received gentamicin by intraperitoneal injection and 8% R. officinalis L. aqueous extract orally (10 mL/kg), the control groups were treated with saline solution (0.9% NaCl) or gentamicin (60 mg/kg).…”
Section: Control Of Body Weight and Dyslipidemiamentioning
confidence: 99%
“…These molecules are responsible for exerting significant antioxidant activity, as well as quercitin, luteolin, kaempferol, and rosmarinic, hydrocafeic and caffeic acids [61]. Thus, R. officinalis L. can protect the organism against hyperlipidemic and hepatotoxic effects promoted by some products, as gentamicin [60]. This antibiotic can affect the liver and enhance the enzymatic activity of aspartate transaminase (AST) and alanine transaminase (ALT), as well as increase the bilirubin level and decrease the protein synthesis.…”
Section: Control Of Body Weight and Dyslipidemiamentioning
confidence: 99%
See 1 more Smart Citation
“…Among the herbs belonging to the Lamiaceae family, rosemary (Rosmarinus officinalis L.) is by far the one to which the highest number of biological activities have been ascribed. In the latest five years, the in-vivo hepato-and hepato-renal protective effects of rosemary have been extensively studied; as example Hegazy et al [426] investigated the preventive effect of the aqueous extract of this herb on the gentamicininduced hepatotoxicity in rats with promising result connecting these activities with the presence in the extract of catechin (37), coumarin (38), cinnamic acid (39), rutin (40), sinapic acid (41) and oleuropein (42), whilst Mohamed et al [427] studied the protection of rosemary ethanolic extract on lead acetate hepatoand nephrotoxicity in male albino rabbits. The authors found that pre-treatment with rosemary extract significantly suppressed levels of hepatic and renal damage products as well as lipid peroxidation.…”
Section: Rosemarymentioning
confidence: 99%